Efficacy, tolerability, and acceptability of bupropion for major depressive disorder: A meta-analysis of randomized-controlled trials comparison with venlafaxine - Narong Maneeton (2018)
Background: Bupropion and venlafaxine are effective antidepressants with unique pharmacological profiles. Objectives: The purpose of this meta-analysis was to determine the efficacy, acceptability, and tolerability of bupropion and venlafaxine therapies for adults with major depressive disorder (MDD). The authors searched clinical trials with low risk of bias, performed from January 1985 to February 2013. Data sources: The searches of MEDLINE, EMBASE, CINAHL, PsycINFO, and Cochrane Controlled Trials Register were conducted in February 2013. Included populations consisted of adult patients with MDD or major depression. Study eligible criteria, participants, and interventions: Included studies were randomized controlled trials (RCTs) comparing bupropion and venlafaxine in adult patients with MDD and offering endpoint results relevant to: (1) severity of depression; (2) response rate; (3) remission rate; (4) overall discontinuation rate; or (5) discontinuation rate due to adverse events. Limitation of language was not utilized. Study appraisal and synthesis methods: The abstracts located from the electronic databases were reviewed. The completed reports from pertinent studies were examined, and essential data were extracted. Based on the Cochrane's bias assessment, risks of bias were assessed. Any study with two risks or more was excluded. Efficacious outcomes included the mean changed scores of rating scales for depression, overall response rates, and overall remission rates. Acceptability was determined by the overall discontinuation rates. The discontinuation rates due to adverse events were the measurement of tolerability. Relative risks (RR) and weighted mean differences or standardized mean differences with 95% confidence intervals (CI) were computed using a random effect model. Results: A total of 1,117 participants in three RCTs were included. Depression rating scales used in one and two studies were the 17-item Hamilton Depression Rating Scale and the Montgomery-Asberg Depression Rating Scale, respectively. The pooled mean changed scores of the bupropion-treated group were comparable to those of the venlafaxine-treated group with standardized mean differences (95% CI) of 0.05 (-0.16 to 0.26). The overall response and remission rates were similar with the RRs (95% CI) of 0.92 (0.79-1.08) and 0.97 (0.75-1.24), respectively. The pooled overall discontinuation rate and discontinuation rate due to adverse events were not different between groups with the RRs (95% CI) of 1.00 (0.80-1.26) and 0.69 (0.44-1.10), respectively. Limitations: The small number of RCTs included in the meta-analysis. Conclusion: According to the limited data obtained from three RCTs, bupropion XL is as effective and tolerable as venlafaxine XR for adult patients with MDD. Further studies in this area should be conducted to confirm these findings. © 2013 Maneeton et al.